2023
DOI: 10.3390/w15213737
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Research Significance of Micro-Nanoparticles in Geothermal Fluids in the Central Area of Shandong Province

Lei Zuo,
Peng Zhang,
Yaqin Wang
et al.

Abstract: The micro-nanoparticles found in geothermal fluids exhibit distinct characteristics that hold great potential for detecting deeply concealed geothermal resources. Utilizing a nanoparticle tracking analyzer (NTA), we conducted observations on karst geothermal fluids collected from the central region of Shandong Province, specifically Jinan and Zibo. Our investigation revealed the presence of a significant quantity of naturally occurring micro-nanoparticles within these geothermal fluids, with particle sizes typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Iron-bearing particles of the same type exhibit certain regularities in morphology; hematite particles often appear as cubic aggregates (Figure 6), and iron oxide particles are in aggregate forms (Figure 7). The above research indicates that the composition of the nanoparticles in groundwater from the recharge area and discharge area is relatively consistent, which is also the same as the nanoparticles found in the hot spring in Northern Jinan (see the details in Zuo et al [27]). These findings indicate that the recharge area and discharge area, as well as the northern geothermal zone, indeed have certain hydraulic connections.…”
Section: Comparison Of Nanoparticle In the Groundwater From Recharge ...supporting
confidence: 69%
See 1 more Smart Citation
“…Iron-bearing particles of the same type exhibit certain regularities in morphology; hematite particles often appear as cubic aggregates (Figure 6), and iron oxide particles are in aggregate forms (Figure 7). The above research indicates that the composition of the nanoparticles in groundwater from the recharge area and discharge area is relatively consistent, which is also the same as the nanoparticles found in the hot spring in Northern Jinan (see the details in Zuo et al [27]). These findings indicate that the recharge area and discharge area, as well as the northern geothermal zone, indeed have certain hydraulic connections.…”
Section: Comparison Of Nanoparticle In the Groundwater From Recharge ...supporting
confidence: 69%
“…Many natural activities can produce nanoparticles, leading to a significant natural The above research indicates that the composition of the nanoparticles in groundwater from the recharge area and discharge area is relatively consistent, which is also the same as the nanoparticles found in the hot spring in Northern Jinan (see the details in Zuo et al [27]).…”
Section: Genesis Nanoparticles In the Groundwater Of The Baotu Spring...supporting
confidence: 58%
“…These nanoparticles are formed from both geochemical and biological processes. Numerous investigations also have shown the presence of a significant quantity of natural in hot spring, such as Tobler et al found natural SiO 2 nanoparticles in the Icelandic geothermal areas (Tobler et al, 2008), Wu et al confirmed natural MnSiO 3 , Fe (1-x) S, SiO 2 , Al 2 O 3 , FeSO 4 and Na 2 CO 3 in Taiwan hot springs (Wu et al, 2016) and Zuo et al found numerous natural carbonates, sulfates, and chlorides nanoparticles occurring in geothermal fluids form the central area of Shandong Province (Zuo et al, 2023). In addition, geothermal energy can make higher geothermal gradient, which can serve as one of the driving forces behind the migration of nanoscale materials (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 98%